2016
DOI: 10.1021/acs.langmuir.5b03437
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization of Dienoyl Lipids Creates Planar Supported Poly(lipid) Membranes with Retained Fluidity

Abstract: Polymerization of substrate-supported bilayers composed of dienoyl phosphatidylcholine (PC) lipids is known to greatly enhance their chemical and mechanical stability, however the effects of polymerization on membrane fluidity have not been investigated. Here planar supported lipid bilayers (PSLBs) composed of dienoyl PCs on glass substrates were examined to assess the degree to which UV-initiated polymerization affects lateral lipid mobility. Fluorescence recovery after photobleaching (FRAP) was used to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…All recovery curves were fitted using both single and double exponential models; in all cases, the double exponential fit produced a higher adjusted coefficient of determination and a more random residuals plot, consistent with previous studies. 29,40,41 Diffusion coefficients (D 1 , D 2 , and D avg ) and percent recoveries are listed in Table 1 for PSLBs doped with 0.6 mol % Rho-PE as a function of DPhPC/bis-SorbPC molar ratio. As the ratio was increased from 10:0 to 0:10, D avg systematically decreased 7-fold.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All recovery curves were fitted using both single and double exponential models; in all cases, the double exponential fit produced a higher adjusted coefficient of determination and a more random residuals plot, consistent with previous studies. 29,40,41 Diffusion coefficients (D 1 , D 2 , and D avg ) and percent recoveries are listed in Table 1 for PSLBs doped with 0.6 mol % Rho-PE as a function of DPhPC/bis-SorbPC molar ratio. As the ratio was increased from 10:0 to 0:10, D avg systematically decreased 7-fold.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, in a recent study, lateral diffusion coefficients (D) were measured before and after UV-initiated polymerization of planar supported lipid bilayers (PSLBs) composed of dienoyl lipids. 29 The D values of lipid probes measured after polymerization were 0.1−0.8 of those measured before polymerization and were indicative of fluidity intermediate between that of an L α phase and an L β phase. Prior work showed that this moderate decrease in fluidity did not adversely affect the activity of some incorporated proteins: (a) The conductance of α-hemolysin ion channels reconstituted into a suspended lipid bilayer (i.e., a black lipid membrane or BLM) composed of bis-dienoylphosphatidylcholine (bis-DenPC) was maintained after polymerization, and bis-DenPC BLMs were found to be highly stable to conditions that readily ruptured unpolymerized BLMs.…”
Section: ■ Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, ion-conductive, aligned hexagonal polymer films via cross-linkable thermotropic (i.e., temperature-dependent and solvent-free) ILCs have also been formed. Literature examples of cross-linked ILC materials from other groups include lyotropic polymerized lipid bilayers, cross-linked thermotropic ILCs with high anisotropic and 3D ionic conductivity, and nanostructured electrochromic poly­(ILC) films …”
mentioning
confidence: 99%